Observational studies of exposure to tobacco and nicotine products: Best practices for maximizing statistical precision and accuracy - Gal Cohen; Steven Cook (iScience)
Summary: Non-randomized observational studies can track risk-induction and -reduction associated with real-world use of non-combusted nicotine and tobacco products. The objective of this analysis was to evaluate the precision and accuracy of recent studies and to identify opportunities for further optimizing future study designs. The ROBINS framework for minimizing statistical bias was translated to specific considerations that spanned the selection and quantification of cohorts, exposure, and outcomes. These principles were then considered within the context of a recent comprehensive meta-analysis, representing 107 observational studies, which evaluated the effects of using electronic cigarettes (ECs), combusted cigarettes (CCs) and dual use of both. The meta-analysis had previously reported the relative risk from all-sources, including tobacco use and non–tobacco use. We now report the product use–specific risk associated with displacing CCs with ECs indicated from the primary references, along with observations regarding the precision of characterization of CC and EC exposure in the cited studies.